“Como se criar?”: possíveis relações entre a formação de professores e a arquitetura escolar em uma periferia de São Mateus/ES - Cruz, Marcelo Silva (2023)
“How to create yourself?” We justify the expression in the title of our research, through the statement of the French philosopher and historian Michel de Certeau (1925 – 1986), when in the introduction of his work “The Invention of everyday life: Arts of doing”, he proposes the internal return, a return inwards, towards self-recognition, as a break with acquired formations, seeking a more autonomous mobilization. This work describes the trajectory of our observations as a researcher, with the purpose of understanding the relationships between teacher training and school architecture in peripheral places, in São Mateus/ES. We looked for objects for our examination in the periphery, due to the bifurcation between the daily life lived in the place and the movement in the school environment. The movements of social actors practicing in these spaces and their life stories are the elements of our script. In addition to Certeau, we used the theoretical contribution of Bruno Zevi, on architecture and spaces; Antonio Viñao Frago and Agustín Escolano, school architecture and the school as culture; Marie-Christine Josso, the formation of the human through narratives; Viola Spolin, theatrical games for teaching.